(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
To investigate the aesthetic preferences of consumers towards various sustainable colors, this study aims to assist designers in gaining a comprehensive understanding of consumers’ color preferences during the development of eco-friendly clothing designs. The study begins by establishing a sustainable color matching scheme for clothing and employs the semantic difference method to select perceptual word pairs. Subsequently, a questionnaire survey is conducted to understand consumers’ perceptual evaluation of sustainable colors in clothing. The study further analyzes and ranks the main factors by quantifying the perceptual evaluation and employing the grey correlation degree method. The results indicate that temperament factor, personality factor, and coordination factor are the primary perceptual factors influencing sustainable color. Among these factors, temperament exhibits the strongest correlation with the degree of liking, followed by personality and coordination. When selecting colors, designers should prioritize low brightness and low purity colors. Additionally, blue-green colors are more favored by consumers. The research findings hold significant implications for guiding designers in enhancing the quality and standard of green clothing design while meeting consumers’ perceptual cognitive requirements.